An experimental study on the impact of security in a multi-hop ad-hoc network on a VoIP data stream - Nuñez, Raymond C. (2008)
In the world of Voice over IP (VoIP), the network has a high impact on the quality of the voice traffic. This is especially true on Mobile Ad-hoc Networks (MANETs) where each mobile wireless node can act as a forwarding router. VoIP has specific requirements that make it highly sensitive to packet loss, latency and jitter. Furthermore, applying security to the routing protocols in a MANET adds additional delay as encryption, decryption, and verification consume additional processor cycles on each mobile node compounded by the number of nodes in the path. In order to assess a network?s ability to transport VoIP traffic, a stream is generated on one side of the network and is captured on the other while logging data and performance metrics as the stream passes through. This allows a controlled flow of traffic to be used to identify areas and events that can impede VoIP traffic. This research attempts to evaluate and compare the reactive MANET routing protocols Ad-Hoc On-Demand Distance Vector (AODV) and Secure AODV (SAODV) using Mean Opinion Score (MOS). It also aims to expand and use the Kasuari emulation framework not only for protocol testing but also for performance evaluation. The analysis of the results shows that the SAODV does not introduce a significant overhead and has nearly the same MOS when compared with AODV. Additional CPU cycles compensated for the overhead caused by encryption, thus protecting SAODV?s audio stream from further degradation.
Thesis (M.S. Computer Science)--University of the Philippines Diliman.
Keywords: Internet telephony -- Security measures